Metal-organic framework-mediated antioxidant enzyme delivery in disease treatment - Jiang Yayun; Ge Qianqian; Sun Xihang; Hong Yang; Hou Zhenping; Li Yuying; Ma Xiancheng; Jiang Qian; Shi Pengjun (Redox Biology)
Excessive reactive oxygen species (ROS) induce oxidative stress (OS), resulting in biomolecular damage. ROS are closely linked to diseases such as inflammatory bowel disease (IBD), diabetes, and cancer. Antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), and glucose oxidase (GOX) play crucial roles in alleviating OS by effectively reducing ROS levels through synergistic action. However, these antioxidant enzymes exhibit poor stability in complex biological environments and lack adequate targeting capability, thereby limiting their applications in disease treatment. Metal-organic frameworks (MOFs) serve as carriers that significantly enhance enzyme stability and targeting ability, thereby boosting catalytic efficiency and therapeutic outcomes. This review discusses the classification of antioxidant enzymes and their role in ROS regulation, the types and physicochemical properties of MOFs, and the assembly methods of enzyme@MOF systems. Furthermore, it examines the potential of integrating MOFs with antioxidant enzymes for the treatment of diseases associated with OS. Although the strategy of enzyme immobilization with MOFs shows great application prospects, further optimization is required in terms of biocompatibility, long-term stability, and delivery efficiency to promote the clinical translation of these results.